2016
DOI: 10.1111/ele.12706
|View full text |Cite
|
Sign up to set email alerts
|

Light asymmetry explains the effect of nutrient enrichment on grassland diversity

Abstract: One of the most ubiquitous patterns in plant ecology is species loss following nutrient enrichment. A common explanation for this universal pattern is an increase in the size asymmetry of light partitioning (the degree to which large plants receive more light per unit biomass than smaller plants), which accelerates the rates of competitive exclusions. This 'light asymmetry hypothesis' has been confirmed by mathematical models, but has never been tested in natural communities due to the lack of appropriate meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
207
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(223 citation statements)
references
References 40 publications
13
207
3
Order By: Relevance
“…For instance, pair members remain strongly associated through the winter and base their behaviour around one another [49]. Birds also appear to shape their breeding positions and territories around their close winter associates, potentially to reduce competition and increase cooperation during breeding [46]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, pair members remain strongly associated through the winter and base their behaviour around one another [49]. Birds also appear to shape their breeding positions and territories around their close winter associates, potentially to reduce competition and increase cooperation during breeding [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Insects often perform best when provided N-enriched foods, experiencing higher growth [1820,46], survival [2124,47], and reproductive rates [22,25]. Contradicting these results, C .…”
Section: Discussionmentioning
confidence: 99%
“…curtipennis foraging effort [49]. Second, N-fertilization increases plant biomass [26], which can in turn reduce grass canopy light and temperature [47,50]. Since grasshopper foraging is temperature-dependent [51], reductions in temperature caused by fertilization could reduce grasshopper foraging intensity or digestion efficiency, yielding no net impact of fertilization on growth.…”
Section: Discussionmentioning
confidence: 99%
“…Because some plants are taller, they receive more light per unit size than do smaller plants, thus precipitating competitive exclusion. Up to now, there has been limited evidence to conclusively demonstrate this mechanism, but a recent study demonstrated that an increase in light asymmetry is the main cause of species loss under nutrient enrichment 9 . DeMalach et al .…”
Section: Threats To Grasslandsmentioning
confidence: 99%
“…DeMalach et al . 9 used a combination of light measurements through the grassland canopy and plant height in fertilised and unfertilised grasslands to calculate light asymmetry and determine the competitive effect, demonstrating that it is an increase in the rate of light decay through the canopy rather than an increase in canopy height that is responsible for the competitive effect of grasses on forbs.…”
Section: Threats To Grasslandsmentioning
confidence: 99%